Characterization of painting pigments and ochres associated with the Hoabinhian archaeological context at the rock-shelter site of Doi Pha Kan (Thailand). (August 2019) - Lebon, M.; Gallet, X.; Bondetti, M.; Pont, S.; Mauran, G.; Walter, P.; Bellot-Gurlet, L.; Puaud, S.; Zazzo, A.; Forestier, H.; Auetrakulvit, P.; Zeitoun, V.
Abstract: The use of ochre in mortuary practices was widespread during prehistory. In northern Thailand, several painted rock-shelters attributed to Iron age or Neolithic cultures have provided burials characterized by the presence of pigment fragments and ochres deposits. In the case of Doi Pha Kan, data collected during excavations have highlighted the important role of ochre in funerary rites dating from 13, 172 to 10, 986 cal BC. The presence of painted panels overhanging Hoabinhian burials raises the question of their chronology and association to painting activities. To investigate this issue at Doi Pha Kan, we applied a multi-analytical approach (optical microscopy, SEM-EDS, Raman spectroscopy, XRF spectroscopy, XRD and μXRD) on painting pigments and ochres associated with a grave (dpk E-5) and the archaeological context to determine the mineralogical and elemental composition of pigment raw materials. We showed that the composition of raw pigments from the archaeological context is homogeneous, suggesting a common geological source characterized by the presence of As. In contrast, pigments on the painted panel have variable compositions indicating that panels were created in different time periods. The pigment used for anthropomorphic figure is the only one similar to the materials identified in the archaeological levels and burial at Doi Pha Kan. Without possibility of direct dating, it is not possible to establish a direct link between the these anthropomorphic figure paintings and mortuary practices, however two painted wall fragments were discovered in the archaeological layers attest to a long tradition of rock painting for at least 13, 000 years at this site. Highlights: Ochre plays an important role in mortuary practices at Doi Pha Kan (Thailand), a painted rock-shelter dated to 13, 000 BP AThe composition of raw pigments from the archaeological context is homogeneous, suggesting a common geological source Pigments on the painted panel have variable compositions indicating that panels were created in different time periods The pigment used for anthropomorphic figures is similar to the composition of archaeological pigments Painted wall fragments discovered in the archaeological layers attest to a long tradition of rock painting at this site